Síntese e caracterização de HDLs de Zn/Al adsolubilizados com óleos essenciais de copaíba ou melaleuca para potenciais aplicações em pomadas dermatológicas - Nogueira, Daiane Amaral de Ramos (2022)
In this work, layered double hydroxide of Zn/Al intercalated with dodecylsulfate ion (DS) in molar ratios 2:1, 3:1 and 4:1 (Zn2+/Al3+) were synthesized by co-precipitation method and adsolubilized with essential oils of copaiba or tea tree in concentrations of 3, 5, 10, 13 and 15% wt/wt to be used as carriers in therapeutic ointments for skin injury treatments. The XRD results showed a diffraction pattern corresponding to the structure of LDHs with the presence of diffraction peaks referring to the basal reflection planes. Typical vibration bands of essential oils presents in FTIR spectra confirmed the adsolubilization process. The Copaíba oil release plateau in the ointment was above 80% at normalized values in a time of approximately 20 h, time required for dissolution and release of molecules adsorbed in the lamellar structure of the material for molar ratios 2:1 and 3:1 and for the release of the solubilized molecules in the interlayer space. while LDH with a 4:1 molar ratio showed slower release and did not reach the plateau in 48 h, as this material has the ability to retain oil molecules in the LDH for longer, causing a slower release in relation to other molar ratios. The TTO oil release curves showed that the Zn4Al/TTO10% LDH was the material more propitious with an 80% release in 28h and reached the plateau at 48h.